An interaction of a NR3C1 polymorphism and antenatal solar activity impacts both hippocampus volume and neuroticism in adulthood - Montag, Christian; Eichner, Markus; Markett, Sebastian; Quesada, Carlos M.; Schoene-Bake, Jan-Christoph; Melchers, Martin; Plieger, Thomas; Weber, Bernd; Reuter, Martin (Frontiers in Human Neuroscience, 2013)
The investigation of the interaction of genes and environment in the context of mental health and personality yields important new insights for a better understanding of human nature. Both antenatal and postnatal environmental factors have been considered as potential modulators of genetic activity. Antenatally, especially smoking or alcohol drinking habits of the mother dramatically influence the health of the child during pregnancy and even later on in life. In the present study we would like to introduce a more “distant” factor that is not under the control of the becoming mother but that nevertheless plays a potential role for the health of the unborn child later on in adulthood. Here, we retrospectively investigate the influence of solar activity (while the child is still in the uterus of the becoming mother) on brain structure (with a focus on hippocampus and amygdala volume) and personality in adulthood. We observe an interaction of a genetic variant (rs41423247) of the glucocorticoid receptor gene (NR3C1) and solar activity in the first trimester after conception on both hippocampal volume and the personality trait neuroticism in adulthood in N = 254 participants. The NR3C1 gene is the focus of interest, because of its influence on the hypothalamic-pituitary-adrenal (HPA) axis and negative emotionality. Carriers of the CC variant of rs41423247 grown in the womb under the influence of high sun radiation (high solar activity) show both the highest hippocampal volume in the left hemisphere and lowest neuroticism scores. The present findings should encourage researchers in psychology and psychiatry to include also environmental influences such as solar activity besides genetics to better understand the etiogenesis of psychiatric disorders.